Description of race cources and estimation of ground reaction forces by GPS-Data and video - Huber, A.; Waibel, K.; Spitzenpfeil, P. (Science and Skiing IV, 2009)
INTRODUCTION: During the entire alpine Ski World-Cup-Season 2006/2007, the German coaches were equipped with a GPS-device to record the coordinates of the turning gates in all races in the disciplines Giant Slalom and Super G. The data of the turning gates in all three dimensions were used to calculate the distances between the gates, angles of the gates, and the radius of the turns. In some races, the video recordings of the two best racers were used to cover the times between the gates. Putting the data together, it is possible to calculate the velocity between gates, the radial acceleration in turns, and to estimate the ground reaction forces of particular racers.